Analysis of speech of stutterers - KN, Shashidhar (Journal of All India Institute of Speech and Hearing)
Studies have been conducted to on several aspects of stuttering. Relationship between linguistic factors and stuttering have also been studied. However, with reference to Kannada language there are only two studies. Therefore it was felt that it is necessary to conduct a study to note relationship between linguistic factors and stuttering in children and adults using Kannada language.